Urethral Leiomyoma: A Benign Smooth Muscle Tumor in Female Urethra - Nazli Hameed; Binyamin Butt (Shalamar Medical & Dental College, Lahore, Pakistan, 2019)
Background: A benign smooth muscle fibroid was found in urethra. The tumor can be seen in females of reproductive age group with a peak incidence reported at 41 years. The rarity is supported by less than a hundred cases reported in literature. Case presentation: In this case report a 48 year old woman presented to us with incontinence and poor urinary stream and was found to have a urethral leiomyoma. The lesion was enucleated and dead space closed. Patients made a smooth postoperative recovery. Conclusion: Urethral leiomyoma is a rare benign tumor affecting females of reproductive years of life. The clinical diagnosis can be aided by endoscopic or radiological investigation. Surgical excision is the preferred treatment with a low Risk of recurrence.